2012
DOI: 10.1088/0953-8984/24/21/215501
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 3d doping on the electronic structure of BaFe2As2

Abstract: BaFe 2 As 2 exhibits properties characteristic of the parent compounds of the newly discovered iron (Fe)-based high-T C superconductors. By combining the real space imaging of scanning tun-neling microscopy/spectroscopy (STM/S) with momentum space quantitative Low Energy Electron Diffraction (LEED) we have identified the surface plane of cleaved BaFe 2 As 2 crystals as the As terminated Fe-As layer-the plane where superconductivity occurs. LEED and STM/S data on the BaFe 2 As 2 (001) surface indicate an ordere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
56
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 43 publications
13
56
0
Order By: Relevance
“…Since Cu 3d states are located deeper below the E F than Co, 6,9,45 the extra d electrons for Cu almost totally locate around the substituted site. Hence, closed 3d shell is observed by XPS and XAS, although there is a little delocated electron introduced by Cu dopant.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since Cu 3d states are located deeper below the E F than Co, 6,9,45 the extra d electrons for Cu almost totally locate around the substituted site. Hence, closed 3d shell is observed by XPS and XAS, although there is a little delocated electron introduced by Cu dopant.…”
Section: Discussionmentioning
confidence: 99%
“…X-ray photoelectron spectroscopy (XPS) and x-ray absorption (XAS) measurements show that Cu 3d states locate at the bottom of the valence band in a localized 3d 10 shell, so that the formal valence state of Cu is +1 and the substitution of Fe 2+ by Cu 1+ results in hole doping. [7][8][9] The theoretical and experimental studies on SrCu 2 As 2 , the end member of Sr(Fe 1−x Cu x ) 2 As 2 series, indicate that it is an sp-band * Corresponding author; Electronic address: chenxh@ustc.edu.cn metal with hole-type carries dominate and Cu in the nonmagnetic 3d 10 electronic configuration corresponds to the valence state Cu 1+ , 7,10,11 which further supports the result of XPS and XAS. In addition, the doping effect of Cu is similar to that of Mn, which is also considered as hole doping and no superconductivity has been found.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…100 Resonant and nonresonant x-ray absorption and emission spectroscopy measurements as well as core and valence level x-ray photoelectron spectroscopy measurements were carried out by McLeod et al 101 on the Fe, Co, Ni and Cu atoms in Ba(Fe 1−x M x ) 2 As 2 crystals with M = Co, Ni and Cu. They found that there is little charge transfer from the dopant atoms to the Fe atoms and that the iron arsenides are not strongly correlated electron systems.…”
mentioning
confidence: 99%
“…As the SDW magnetic character of the Fe 3d electrons is nearly unaffected by the magnetic field (not shown), we attribute this spin-dependent scattering mechanism to the Cu 2+ (s = 1/2) local moments shown by recent ESR experiments, which directly probe the Cu oxidation state [16]. The ESR data are in contrast to previous reports based on ARPES, XAS and NMR measurements, which suggest that the Cu atoms are in the Cu 1+ oxidation state [31,[34][35][36]. However, the data reported here is consistent with a Cu 2+ spin-dependent scattering mechanism.…”
Section: Resultsmentioning
confidence: 55%